THE PREPARATION, PURIFICATION, AND AMINO ACID SEQUENCE OF A POLYPEPTIDE RENIN SUBSTRATE - Skeggs, Leonard T. (The Rockefeller University Press, 1957)
A purified preparation of a polypeptide renin substrate prepared by tryptic degradation of the protein renin substrate has been analyzed by the fluorodinitrobenzene method and after degradation with renin, carboxypeptidase, and phenylisothiocyanate, has been found to possess the amino acid sequence; asp-arg-val-tyr-ileu-his-pro-phe-his-leu-leu-val-tyr-ser. The first 10 of these amino acids constitutes hypertensin I which is released by cleavage of the leucyl-leucine bond by renin. The remaining 4 amino acids, leu, val, tyr, ser, apparently link hypertensin I to the protein renin substrate.